Variations in Patient Safety Climate in Chinese Hospitals. Issue 3 (April 2021) - Zhu, Junya; Li, Liping; Zhou, Zehui; Lou, Qingqing; Wu, Albert W.
Abstract : Objectives: Patient safety climate is associated with patient outcomes in hospitals around the world. A better understanding of how safety climate varies within and across hospitals will help identify improvement opportunities. We examined variations in safety climate by work area and job category in Chinese hospitals. Methods: We administered the Chinese Hospital Survey on Patient Safety Climate in 2011 to workers in 6 hospitals in China, with completed surveys from 1464 (86% response). We calculated the percent positive response for survey items and dimensions among hospitals and compared this across work areas and job categories using general linear models. Results: Overall, 68% of responses suggested the presence of a positive safety climate. The percent positive responses were highest for organizational learning (86.1%) and unit management support for safety (84.5%) and lowest for staffing (30.6%) and error reporting (44.5%). Workers in surgical units, intensive care units, operating rooms, and emergency departments were slightly more negative regarding overall safety climate than those in medical and ancillary units. Physicians reported worse perceptions than nurses or other hospital workers on all dimensions except for unit management support for safety and communication and peer support. Conclusions: The perceived problem with staffing in Chinese hospitals was consistent with other studies. The lack of positive responses for error reporting may indicate a lack of awareness of the importance of learning from and reporting minor events and near misses. Variations within and across hospitals in safety climate suggest that improvement interventions should be tailored to individual units and professional groups. Abstract : Supplemental digital content is available in the text.